Systematyka operowych duchów - Golianek, Ryszard Daniel (Poznańskie Studia Polonistyczne. Seria Literacka, 2022)
Ghosts have been an attractive element of operatic dramaturgy since the beginning of the genre’s history, and their stage presence influences the metaphysical and fantastic features of the works. In seventeenth- and eighteenth-century operas, conventional forms of musical presentation and characteristics of ghosts were developed, and in the nineteenth century a conventionalized method of musical presentation of ghosts in opera was shaped, which was also due to the great popularity of the theme of various spectres and phantoms in romantic culture. The proposed systematics concerns the ghosts presented in operatic works. Three criteria of division have been introduced: the existential status of ghosts, their number (singularity or multiplicity), and the types of afterlife the ghosts are associated with. The systematics is accompanied by the distinction of the means of musical characteristics used by opera composers in order to suggestively represent ghosts in their works.